Protection of 'Whistleblowers' Identity - Željko Mirjanić; Jasna Čošabić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
A whistleblower decides to reveal wrongdoings, having in mind the identity and labour legal protection and the corresponding legal praxis, either using the public or anonimous reporting. Confidentiality is based on rules that whistleblowers personal data are available to authorised subjects only, and not to a wider public. Protection of whisleblowers personal data is assured by officials' acting upon anonymous reports. Anonimity as a mode of whislteblowers identitity protection, is important when speaking of reporting to public which has the right to receive information, and it technically becomes increasingly facilitated by the use of information technologies. The central part of the paper relates to analysis of the adequate protection of personal data and privacy of whistleblowers, which is in special focus of the European Union, through the work of European Data Protection Supervisor and the imlementation of relevant legislation, having in mind that whistleblowing procedures contain processing of sensitive personal information. Legal analyses of the laws and relevant material has showed that the protection of identity and privacy of whistleblowers in posttransitional countries of the Southeast Europe is unreliable, and they do not enjoy the expected legal security in accordance with proclaimed strategies on fight against corruption.
Keywords: K31; 330; protection of whistleblowers identity; protection of whistleblowers privacy; anominoys reporting of corruption; reporting public interest violation